What Do We Mean by Behavioral Disinhibition in Frontotemporal Dementia? - Magrath Guimet, Nahuel; Miller, Bruce L.; Allegri, Ricardo F.; Rankin, Katherine P. (Frontiers in Neurology, 2021)
Behavioral variant frontotemporal dementia, unlike other forms of dementia, is primarily characterized by changes in behavior, personality, and language, with disinhibition being one of its core symptoms. However, because there is no single definition that captures the totality of behavioral symptoms observed in these patients, disinhibition is an umbrella term used to encompass socially disruptive or morally unacceptable behaviors that may arise from distinct neural etiologies. This paper aims to review the current knowledge about behavioral disinhibition in this syndrome, considering the cultural factors related to our perception of behavior, the importance of phenomenological interpretation, neuroanatomy, the brain networks involved and, finally, a new neuroscientific theory that offers a conceptual framework for understanding the diverse components of behavioral disinhibition in this neurodegenerative disorder.